Complex Boron-Containing Molecules through a 1,2-Metalate Rearrangement/anti-SN2′ Elimination/Cycloaddition Reaction Sequence - Tillin, Chloe; Bigler, Raphael; Calo-Lapido, Renata; Collins, Beatrice S. L.; Noble, Adam; Aggarwal, Varinder K. (Synlett, 2019)
The three-component coupling of benzylamines, boronic esters, and 4-phenyl-3H-1,2,4-triazole-3,5(4H)-dione (PTAD) is reported. The boronate complex formed from an ortho-lithiated benzylamine and a boronic ester undergoes a stereospecific 1,2-metalate rearrangement/anti-SN2′ elimination in the presence of an N-activator to provide a dearomatized tertiary boronic ester. Interception of this dearomatized intermediate with a dienophile leads to stereopredictable cycloaddition reactions to generate highly complex three-dimensional boron-containing molecular structures. When enantioenriched α-methyl-substituted benzylamines are employed, the corresponding cycloaddition adducts are formed with excellent enantiospecificities.
Keywords: cycloaddition; 1,2-metalate rearrangement; phenyltriazoledione; benzylamines; boronic esters; multicomponent reaction